Site-specific recombinase strategy to create induced pluripotent stem cells efficiently with plasmid DNA - Karow, Marisa; Chavez, Christopher L.; Farruggio, Alfonso P.; Geisinger, Jonathan M.; Keravala, Annahita; Jung, W. Edward; Lan, Feng; Wu, Joseph C.; Yanru, Chen Tsai; Calos, Michele P. (Stem Cells, 2011)
Induced pluripotent stem cells (iPSCs) have revolutionized the stem cell field. iPSCs are most often produced by using retroviruses. However, the resulting cells may be ill-suited for clinical applications. Many alternative strategies to make iPSCs have been developed, but the nonintegrating strategies tend to be inefficient, while the integrating strategies involve random integration. Here, we report a facile strategy to create murine iPSCs that uses plasmid DNA and single transfection with sequence-specific recombinases. PhiC31 integrase was used to insert the reprogramming cassette into the genome, producing iPSCs. Cre recombinase was then used for excision of the reprogramming genes. The iPSCs were demonstrated to be pluripotent by in vitro and in vivo criteria, both before and after excision of the reprogramming cassette. This strategy is comparable with retroviral approaches in efficiency, but is nonhazardous for the user, simple to perform, and results in nonrandom integration of a reprogramming cassette that can be readily deleted. We demonstrated the efficiency of this reprogramming and excision strategy in two accessible cell types, fibroblasts and adipose stem cells. This simple strategy produces pluripotent stem cells that have the potential to be used in a clinical setting. © AlphaMed Press.
CRIS-Team Scopus Importer:2025-02-10
Keywords: Adipose-derived mesenchymal stem cells; Induced pluripotent stem cells; Nonviral reprogramming strategy; Phage integrase